Embedding the Management System Information into Circular Education System through the Smart IoT: A Front Analysis - Tsaniya, Uswatul Wadhichatis; Rahaeni Putri, Fauziah Eka; Candrikaningtyas, Shofia; Susilo, Herawati (IC-ITECHS, 2024)
This research explored how to embed the management system information into circular education system through the smart IoT. Besides, the front analysis of this research aimed to determined what form of IoT that educators need to help them in organized their system information. This research involving qualitative descriptive methods to get the analytical profound through survey technic within cross sectional design. To harvest the front analysis, this research employed 54 educators from any background study within 54 different school’s department consist of public and private schools. The results show that 85.19% of respondents has been including IoT in their school activity, 5.56% occasionally used IoT, and 9.26% not using IoT yet. The majority of IoT that used are projectors, laptop and CCTV. Besides, the platform that usually used are google and YouTube. In the context of information systems management, 100% of educators argue that they need for specialized IoT that can integrate all learning information systems including learning materials, grades, attendance, and tracking students’ activities. This will enable the information systems management to be transparent and easily accessible to all stakeholders in a circular education system. Based on survey data analysis, teachers expressed a desire for a specialized platform that could involve parents more actively. Additionally, by involving parents, educational transparency can be synergized effectively, ensuring a more robust circular education system. In conclusion, this research recommends for future IoT development to create the IoT that consist of a complete school information management system, and it can be used by students, teachers, and parents, while keeping everyone's information private.